Evaluation of the Use of a Hypertension Control Program Using the Walet Method - Liss Dyah Dewi Arini; Linda Widyaningrum; Darah Ifalahma; Yeni Nurmalitasari; Azahra Salma Salsabila Putri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Hypertension is a condition that is often found in health services. Hypertension is a condition when blood pressure in the blood vessels chronically increases. Many risk factors can cause hypertension, including age, race, gender, lifestyle, sodium consumption, smoking, alcohol consumption, stress level, and education. The urgency of this research is the large number of hypertension patients at the Purwodiningratan Surakarta Health Center and it is increasing almost every year. From the initial survey at the Purwodiningratan Surakarta Community Health Center, data was obtained that the number of hypertension patients over the last five years has increased, decreased, then increased again. This is supported by data on the number of hypertension patients in 2019 as many as 311, in 2020 as many as 214, in 2021 as many as 319, in 2022 as many as 125 and in 2023 up to now there are 335. The objective problem in this research is the number of patients with the disease. Hypertension increases from year to year, so research is needed on the relationship between knowledge, attitudes and family support and efforts to control hypertension. The importance of this research is as an effort to control hypertension which continues to increase from year to year by means of interviews and distributing leaflets with the aim of approaching the community. The aim of this research is to analyze how much impact the hypertension control program using the walet method (interviews and leaflets) has on the community. The achievement stages in this research are for the approach used in this research, namely cross sectional. The sample in this study was employees of the Purwodiningratan Health Center, totaling 41 respondents. The sampling technique uses the accidental sampling method based on inclusion and exclusion criteria. The statistical test used is the T test followed by a linear regression test at a significance level of 0.05.